Education 4.0 framework for sustainable entrepreneurship through transdisciplinary and abductive thinking: a case study - Torres-Sánchez, Patricia; Juárez, Antonio Marcelo; Miranda, Jhonattan (Frontiers in Education, 2024)
The global challenges and problems that threaten sustainability and human well-being demand the provision of creative, innovative, and affordable solutions so that they are within the reach of different levels of society. From the point of view of Higher Education, this is a major challenge since it is responsible for training new generations with the competencies and knowledge that allow them to respond to contemporary challenges and problems. This study provides a framework to promote sustainable entrepreneurship through transdisciplinary and abductive thinking. This combination of approaches will allow students to identify, analyze, and understand contemporary problems and, through a systematized process based on the "design thinking" design model, propose creative, innovative, and affordable solutions that can be implemented through entrepreneurship mechanisms. The identified findings that will be presented in this work are (i) the relevance of the Education 4.0 model as a reference to promote transdisciplinarity in a current teaching-learning context, (ii) The relevance of "design for sustainable development" as a trigger for sustainable entrepreneurship, (iii) The formation of desirable competencies in the profile of the higher education student based on transdisciplinarity and abductive thinking within the active learning process, and (iv) quantitative and qualitative measurement that allows measuring acceptance and evaluation of the long-term sustainability of the solutions obtained. This work will present the implementation of the proposed framework through a case study. This case study allowed us to identify elements of the proposed reference framework. The case study will address the problem of water scarcity and pollution, describing initiatives to achieve ODS 6, where it explains how sustainable and visionary solutions can be forged through transdisciplinary collaboration and abductive thinking. The project named "STEAM-mural fountain" done by a transdisciplinary working team between academiasociety-industry is described, which aims to make technological advances in water treatment and monitoring visible to society.